THE PROBLEM OF COMPLEXITY IN CRIMINOLOGY: ANALYSIS OF THE PAST, ASSESSMENT OF THE PRESENT AND A LOOK INTO THE FUTURE (Bulletin of criminological association of Ukraine, 2025)
This article, based on the results of theoretical and empirical research, attempts to evaluate the breadth and depth of understanding the issue of complexity and the comprehensive approach in the field of criminology. Arguments are presented regarding the appropriateness of studying the state of scientific development of the problem of complexity. The characteristics of an intersystem, sectoral-subject-chronological approach to understanding the announced issues are revealed. The author offers a general understanding of complexity and the comprehensive approach. Key scholars and their scientific works, which directly or mostly indirectly relate to the problem of complexity, are listed. The article outlines the four main stages in the formation and development of philosophical and criminological knowledge about complexity. Attention is drawn to the significance of general scientific systems methodology for a deeper understanding of the heuristic potential of the comprehensive approach in general and complexity in particular. The study of theoretical and methodological problems of complexity can be excluded from the implementation of the systematic scientific approach, as well as the consideration of this crisis problem through the prism of a special systemic criminological object (formation). The development of scientific knowledge about complexity and systematicity has gone through decades of conventional historical eras: the initial (Antique), middle (modern era), main (from the middle of the 20th century to the present) and modern stages. Currently, the increase in knowledge about the problem of complexity in criminology can be productive provided that the phenomenon of crime is recognized as a complex social system, which, according to the dialectical law of unity and struggle of opposites, is opposed by another, criminological, system. It consists of several interconnected complexes that closely interact with each other and are aimed at achieving a single systemic goal - the protection of human and civil rights and freedoms, limiting the spread of criminal offenses and reducing their negative social consequences. The prospects for further research into the specified scientific matter have been outlined. Promising directions for increasing scientific knowledge in this area are the justification of the application of complexity at all levels of the criminological system of Ukraine in order to achieve the effectiveness of criminological doctrine, criminological legislation, criminological policy, criminology as an academic discipline, criminological worldview, and criminological activity.
Keywords: complexity; comprehensive approach; systemicity; systems approach; complexity science; methodology; criminological system; criminology; crime; criminal unlawfulness